Causal relationship between the composition of the Gut Microbiota and central precocious puberty: a two-sample Mendelian randomization study - Chen, Minhong; Huang, Xueqin; Huang, Wanhong; Ding, Chuangang (Frontiers in Pediatrics, 2024)
Previous observational research has demonstrated a possible association between the gut microbiota (GM) and central precocious puberty (CPP). Nevertheless, whether there is a causal relationship between the GM and CPP is uncertain due to the possibility of confounding factors influencing the result.We collected summary data from genome-wide association studies of the GM (MiBioGen, n=18,340) and CPP (FinnGen Consortium, 185 case groups and 395,289 controls). Most of the participants were of European origin. Mendelian randomization analysis was utilized to investigate the causal relationship between the GM and CPP using the inverse-variance weighted average technique, the weighted median, and Mendelian randomization Egger. The reliability of the results was evaluated using the leave-one-out test and sensitivity analyses, including heterogeneity and horizontal pleiotropy testing.According to the inverse-variance weighted average technique, there was a substantial correlation between CPP and the composition of the GM. Specifically, the relative abundance of the genus Bacteroides (OR 0.222, 95% CI 0.06-0.822, P=0.024) and Alistipes (OR 0.197, 95% CI 0.056-0.697, P=0.012), and others, showed significant